Belimumab: a step forward in the treatment of systemic lupus erythematosus. (4th May 2021) - Depascale, Roberto; Gatto, Mariele; Zen, Margherita; Saccon, Francesca; Larosa, Maddalena; Zanatta, Elisabetta; Bindoli, Sara; Doria, Andrea; Iaccarino, Luca
ABSTRACT: Introduction : Systemic Lupus Erythematosus (SLE) is a chronic B cell-mediated autoimmune disease which can potentially involve several organs and systems. The development of SLE is associated with a complexity of genetic, hormonal and environmental factors leading to immune deregulation and production of autoantibodies. Therefore, novel therapies have focused on B cells as key effectors of SLE pathogenesis. Belimumab is a fully humanized monoclonal antibody that antagonizes B-lymphocyte stimulator (BLyS); it is the first and the only biological drug approved for SLE in over 50 years. Areas covered : In this review we discuss the pharmacological properties of belimumab, new recommendations for its use in clinical practice and its evidence of efficacy and safety based on clinical trial and real-life data. Expert opinion : Efficacy and safety of belimumab in clinical practice have been well established. To date, it is known that early introduction of belimumab in SLE can maximize the efficacy of the drug. A number of questions are still open, such as the timing of belimumab discontinuation and its possible association with other biological drugs, which need to be assessed in future studies.